Developing novel SNAP tag-based antibody fusion proteins directionally conjugated to fluorophores for immunophenotyping of acute myeloid leukemia - Bvudzijena, Tatenda Lovemore (Institute of Infectious Disease and Molecular Medicine, 2025)
Acute Leukemia comprising of acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL), represents a clonal malignant transformation of hematopoietic cells originating in the bone marrow or lymphoid organs. This is often associated with fundamental genetic abnormalities, and these malignancies are also characterised by persistent proliferation of hematopoietic progenitor cells or maturation arrest at a particular developmental stage, which is specific to each subtype of leukemia. The treatment strategies for acute myeloid leukemia include chemotherapy, bone marrow transplantation, radiotherapy, and immunotherapy, with current research focusing on antibody-based immunotherapy because of its advantages including higher tumour selectivity and increase of drug tolerability. Acute leukemia is diagnosed by combining information from the patient's past medical records, clinical presentations and laboratory results from the studies performed by a pathologist. Pathologist-led studies include haematological investigations like the total blood count, meticulous peripheral blood film review and bone marrow aspiration smear examination. Specific genetic abnormalities linked to AML can be identified through molecular genetic tests, including chromosomal analysis, next-generation sequencing, real-time polymerase chain reaction and cytogenetic analysis. Immunophenotyping by flow cytometry and immunohistochemistry can be used to identify specific proteins or antigens upregulated in AML. In low and middle-income countries, particularly Africa, AML diagnosis is primarily based on leukemic cells or blast morphology, which has significant drawbacks in terms of providing accurate and timely diagnosis. This method utilizes the identification of myeloid blasts primarily through their visual characteristics under the microscope and counting them in bone marrow aspirate samples stained with a suitable Romanowsky stain, such as the Wright-Giemsa stain. Additionally, molecular genetic testing, mostly (RT) polymerase chain reaction (PCR), is also being utilized for AML diagnosis. Using advanced technologies like flow-cytometric immunophenotyping and immunohistochemistry is limited due to the current costs of antibody-based diagnostics in these already strained developing countries' economies Utilizing immunophenotyping by flow cytometry and immunohistochemistry would allow clinicians to clearly define each subtype of acute leukemia, timely diagnose the disease, and initiate therapy on time. These methods utilise monoclonal antibodies targeting uniquely overexpressed markers on leukemic blasts. To address the challenges posed by the costs and limited availability of antibody-based immunodiagnostics in Africa, an alternative approach would be the use an easy-to-tailor fashion of smaller antibody fragments (single chain variable fragments) coupled with a SNAP tag, which can be readily produced recombinantly under cost-controlling conditions. SNAP-tag is a modified version of the human DNA repair enzyme alkylguanine-DNA alkyltransferase (AGT), which reacts specifically with O6-benzylguanine (BG)-modified molecules via irreversible transfer of an alkyl group to a cysteine residue within its active site. Benzylguanine can be chemically attached to a variety of synthetic labels, such as fluorophores. SNAP-tag can be coupled to scFvs (single chain variable fragments), forming unique SNAP tag antibody fusion proteins which undergo self-labelling covalent conjugation reactions with benzylguanine derivatives, and this provides an innovative alternative approach to develop next-generation recombinant immunodiagnostics targeting different biomarkers upregulated in AML. Therefore, this study aimed to explore SNAP tag-based antibody fusion proteins as supplementary or companion diagnostic tools for acute myeloid leukemia targeting cluster of differentiation 14 (CD14), myeloperoxidase (MPO), and the human leukocyte antigen DR (HLA-DR) which are antigens overexpressed on leukemic cells. The variable gene sequences encoding for scFv antibody fragments were obtained from publicly available resources (patents, journals, and antibody databases) and were fused to SNAP by in-silico expression plasmid design. The SNAP fusion protein encoding open reading frames (ORFs) were then cloned into the pCB plasmid vector backbone, containing all the unique features for protein expression in mammalian systems. Following that, scFv-SNAP fusion proteins were generated by transfecting mammalian HEK 293T cells with the recombinant plasmids containing an Ig Kappa leader, which allowed secretion of the proteins into the cell culture supernatant. After extraction, proteins were purified using immobilised metal affinity chromatography (IMAC) and characterised by SDS-PAGE and western blot before being conjugated to BG Alexa fluorophores. Proof of binding of the generated fluorescently labelled SNAP fusion proteins was demonstrated in vitro using leukemic cell lines for CD14 and MPO, while peripheral blood mononuclear cells were used for HLA-DR through confocal microscopy and flow cytometry. The results of the study demonstrated specific binding of the newly generated SNAP fusion proteins, confirming their suitability for diagnostic applications. The future direction of the study will involve testing the generated fusion proteins on South African leukemia patient samples to determine the disease subtypes and comparing them with already existing tools. Additionally, developing new bivalent formats to increase affinity is a potential avenue for future research. In summary, the use of SNAP fusion proteins promotes local development and invention of next generation immunodiagnostics and therapeutics in Africa, and this could be considered as a cost-containment strategy for cancer remedies which are being priced for the first-world markets.